Analysis of Determinants of Artificial Income Smoothing Among Manufacturing Companies for the Period 2018-2020 - Rini Tri Hastuti; Augustpaosa Nariman; Joan Ananda (International Journal of Application on Economics and Business, 2023)
The purpose of my study is to empirically examine the impact of firm size and liqudity on artificial income smoothing practices and to test the capability of institutional ownership in moderating the impact of firm size and liquidity on artificial income smoothing practices. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 – 2020. This study used a purposive sampling technique based on criteria and obtained a sample of 72 observational data with a total of 216 data for three years. The data used are secondary data in the form of financial statements and processed using econometrics views (E-Views) software versi 12. The results showed that firm size had a significant negative impact on income smoothing. Meanwhile, liquidity does not have a significant impact on income smoothing. Institutional ownership cannot moderate the relationship between firm size and liquidity on artificial income smoothing.